2018
DOI: 10.1007/s12031-018-1124-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of a VGF/BDNF/TrkB Autoregulatory Feedback Loop in Rapid-Acting Antidepressant Efficacy

Abstract: Members of the neurotrophin family and in particular brain-derived neurotrophic factor (BDNF) regulate the response to rapid- and slow-acting chemical antidepressants and voluntary exercise. Recent work suggests that rapid-acting antidepressants that modulate N-methyl-D-aspartate receptor (NMDA-R) signaling (e.g., ketamine and GLYX-13) require expression of VGF (non-acronymic), the BDNF-inducible secreted neuronal protein and peptide precursor, for efficacy. In addition, the VGF-derived C-terminal peptide TLQP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 68 publications
(124 reference statements)
1
35
0
1
Order By: Relevance
“…Given the decrease of BDNF in depression pathogenesis, we next decided to evaluate whether Old mice exhibited lower amount of this neurotrophin. The results show an age‐associated decline of BDNF in brain homogenates of Old MRL/lpr (about 1.8‐fold, p < 0.01) as evidenced by immunoblotting analysis ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the decrease of BDNF in depression pathogenesis, we next decided to evaluate whether Old mice exhibited lower amount of this neurotrophin. The results show an age‐associated decline of BDNF in brain homogenates of Old MRL/lpr (about 1.8‐fold, p < 0.01) as evidenced by immunoblotting analysis ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Beside behavioral signs, activation of inflammatory/oxidative stress pathways, alteration of brain n‐6/n‐3 PUFA ratio, and MUFA/SFA content (e.g., DHA; C22:6 n‐3, Oleic, C18:1; Palmitic, C16:0; stearic acid, C18:0) underlie pathology onset and progression. In addition, several parameters involved in brain functioning (brain‐derived neurotrophic factor, BDNF; Tropomyosin receptor kinase B receptor, TrkB), synaptic transmission, and cholinergic signaling (acetylcholinesterase activity, AChE) have been associated with depression pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Could the antidepressant actions of intra-vmPFC TLQP-62 also be dependent on BDNF trafficking and secretion in this region? Previous studies strongly suggest that TLQP-62 may be a critical component of a positive autoregulatory feedback loop that potentiates local BDNF synthesis and secretion and BDNF/TrkB signaling [60], regulating depressionrelated behaviors and memory. Moreover, we found that local BDNF knockdown abolishes increased GluR1 levels in vmPFC synaptosomes 8 days after TLQP-62 infusion.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that VGF and its C-terminal peptide TLQP-62 in the vmPFC potentially increase intracellular Ca 2+ levels via IP 3 -mediated Ca 2+ release from ER, and/or via Ca 2+ influx mediated by SOCE and/or TRPC mechanisms, which subsequently stimulate BDNF secretion. This promotes BDNF/TrkB signaling and mTOR pathway activation, resulting in increased expression and phosphorylation (Ser845) of GluR1, stimulating synaptic trafficking of GluR1 and GluR1dependent synaptic potentiation [58], thus regulating depressionrelated behaviors and the response to ketamine [10,60].…”
Section: Discussionmentioning
confidence: 99%
“…But also, increased hippocampal BDNF and VGF seemingly play a crucial role the rapid anti‐depressant effects of ketamine (Jiang et al . ). Perhaps future studies using this model of hippocampal CRTC1 modulation will investigate the anti‐depressive effects of ketamine.…”
mentioning
confidence: 97%